2010
DOI: 10.1016/j.jtcvs.2010.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Improved left ventricular unloading and circulatory support with synchronized pulsatile left ventricular assistance compared with continuous-flow left ventricular assistance in an acute porcine left ventricular failure model

Abstract: Objective: Controversy exists regarding the optimal pumping method for left ventricular assist devices. The purpose of this investigation was to test the hypothesis that pulsatile left ventricular assist synchronized to the cardiac cycle provides superior left ventricular unloading and circulatory support compared with continuous-flow left ventricular assist devices at the same level of ventricular assist device flow. Methods: Seven male pigs were used to evaluate left ventricular assist device function using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 25 publications
(28 reference statements)
0
39
0
Order By: Relevance
“…Modulation of blood pump motor speeds/flow has been suggested as a potential mechanism to artificially increase vascular pulsatility in both ventricular assist devices 2,5,19,24,26,33,34 and total artificial heart. 10,16,17,27 Flow modulation of ventricular assist devices are affected by the timing of flow modulation to the native myocardial contraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modulation of blood pump motor speeds/flow has been suggested as a potential mechanism to artificially increase vascular pulsatility in both ventricular assist devices 2,5,19,24,26,33,34 and total artificial heart. 10,16,17,27 Flow modulation of ventricular assist devices are affected by the timing of flow modulation to the native myocardial contraction.…”
Section: Introductionmentioning
confidence: 99%
“…Early VAD modulation strategies focused on asynchronous modulation of LVAD flow as it was simpler to implement. 2, 24 Cox et al, 5 Letsou et al, 19 and Shi et al 26 simulated sinusoidal synchronous LVAD flow modulation but did not vary the timing of LVAD flow modulation. Vandenberghe et al varied the timing of synchronous support but did not vary the LVAD flow modulation amplitude or pulse width.…”
Section: Introductionmentioning
confidence: 99%
“…in which SHE represents the extra energy required for generation of pulsatile flow (PF) in terms of energy (not pressure) units and is thus a physiologically relevant measure of pulsatility because the generation of PF in the body is dependent on an energy gradient rather than a pressure gradient [23]. …”
Section: Methodsmentioning
confidence: 99%
“…It has been postulated that within clinical operating ranges, pulsatile flow pumps provide more flow, and this may account for the differences in unloading. This issue was addressed by Letsou et al [36], who compared hemodynamics in seven male pigs supported with pulsatile flow or continuous flow LVADS and found that at the same flow rate, pulsatile flow LVADs demonstrated a higher mean aortic pressure and total cardiac output, while the left atrial pressure was lower. The effects of decreased ventricular unloading were nicely illustrated by the Columbia group, which found lower levels of serum brain natriuretic peptide and extracellular matrix biomarkers in 31 pulsatile flow as compared with 30 continuous flow LVAD patients [37].…”
Section: Ventriclementioning
confidence: 99%